Portal Vein Thrombosis in Liver Cirrhosis. Part 1: Epidemiology, Pathogenesis, Clinic, Diag-nosis, Impact on Prognosis - A. V. Yagoda; P. V. Koroy; L. S. Baisaeva; T. R. Dudov (SINAPS LLC, 2024)
Portal vein thrombosis is the most common thrombotic complication in patients with liver cirrhosis, especially in cases of severe forms. The pathogenesis is multifactorial in nature, it determined by a change in the balance between the coagulation and anticoagulation systems. Thrombosis is often asymptomatic and is accidentally detected, although it can be complicated by varicose bleeding, intestinal ischemia, and portal biliopathy. Ultrasound Doppler examination is a screening method, as an alternative, computed tomography and magnetic resonance imaging are used. The review highlights data on epidemiology, risk factors, clinical features, and diagnosis of portal vein thrombosis in patients with liver cirrhosis. The data on the effect of portal vein thrombosis on the progression of liver cirrhosis and the survival of patients, including after liver transplantation, are presented.